2003
DOI: 10.1154/1.1572487
|View full text |Cite
|
Sign up to set email alerts
|

Rietveld refinements of a new solid solution Ba(3−x)Srx(PO4)2 (0≤x≤3)

Abstract: Ba(3−x)Srx(PO4)2 orthophosphates (0≤x≤3) have been prepared by solid state reaction. The final temperature was 1000°C. The X-ray diffraction analyses show the existence of a continuous solid solution. Ba(3−x)Srx(PO4)2 orthophosphates (0≤x≤3) crystallize in the hexagonal system with the space group R3m. Their structure is based on a three-dimensional framework constructed of infinite layers of Ba1/Sr1O12 linked and parallel to infinite layers of Ba2/Sr2O10 polyhedra and PO4 tetrahedra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…2. A trial bond length-stretching wavenumber trend is defined on the basis of a solid solution series (barium-strontium and strontium-calcium for orthophosphates 8,9,28 and calcium-cadmium for pyrophosphates 29 ) (see b in Tables 2 30 -48 and 3 29,49 -66 for explanation of initial assignments in each data set). 3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2. A trial bond length-stretching wavenumber trend is defined on the basis of a solid solution series (barium-strontium and strontium-calcium for orthophosphates 8,9,28 and calcium-cadmium for pyrophosphates 29 ) (see b in Tables 2 30 -48 and 3 29,49 -66 for explanation of initial assignments in each data set). 3.…”
Section: Resultsmentioning
confidence: 99%
“…Good spectral resolution in the case of Raman spectra was chosen to be limited to values better than 3 cm 1 . These data were supplemented by our experimental measurements on samples prepared by solid-state techniques and characterized by powder x-ray diffraction (Rietveld method) 8,9 and Raman spectroscopy. 10…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is comprised of [Me (1) (VO 4 ) 2 ] 4− layers linked into a crystal network by Me 2+ (2) cations. Manoun et al and Popovic et al reported previously on the solid solution between isostructural phosphates substituting barium with strontium in Ba 3 (PO 4 ) 2 :Ba 3−x Sr x (PO 4 ) 2 [14,15]. Using Raman spectroscopy and X-ray diffraction techniques, the results showed continuous solid solutions.…”
Section: Introductionmentioning
confidence: 88%